Study the impact of crude oil on some physiological activities of Oscillatoria splendida - Hammed S. Khamees; Ali Muayad Sultan; Ayman A. Saleem (Tikrit Journal of Pure Science, 2023)
The effect of different concentration of crude oil had been examined upon Oscillatoria splendida, it was depended upon measuring Growth as optical density, Chlorophyll, Phycocyanin and Protein concentration as an Physiological activities indicator of crude oil effects on Oscillatoria splendida, in addition to morphological changes. The growth optical density in the control sample in the day 30 was (0. 34), while it was (0.148) & (0.08) at 0.25% & 0.5% of crude oil respectively, 41% of chlorophyll concentration has been reduced under effect of 0.25% of crude oil, and reduction 63% of chlorophyll concentration with treatment 0.5%. Protein was reduced 45% at 0.25%, and 82% at 0.5% of crude oil. It was observed reduction growth, chlorophyll, phycocyanin as well as the protein concentration to a minimum under the influence of crude oil treatment 1% and 2% respectively. As well as the absorption spectrum infrared by FTIR show there were absence of methyl group CH3 at (2950 cm-1), (2870 cm-1) and other bundle such as (2300) cm-1, (1500) cm-1, and this is could due to consumed by this species. With appearance a new compounds at 2400 cm-1 and 800 cm-1. Morphologically Observed that the cells within the filament appearance clearly.